Editorial (2012)
Dear reader, On October 5, 2012, fish farmers, entrepreneurs, technicians, researchers, and students came together  for a meeting in Villavicencio from different regions of the country to attend  the XVIII Conference on Fish Farming of the University of the Llanos. With justifiable pride, research groups attached to the IALL (Aquaculture Institute of of the Plains) presented to the community the results of their research at this important event, which has become the specialized meeting with the most tradition in Colombia’s fish farming. It was an academic event of great institutional and human significance. As a recognition of the 18 years of the event, the Direction General de Investigations wanted to add to it through the Revisit Orinoquia, whose editorial committee decided to publish and make available a Supplement to the Revisit Orinoquia dedicated to the XVIII Conference on Fish Farming of the University of the Llanos; that you now have in your hands to read.